Caracterização da dupla permeabilidade de solos com Caatinga e pastagem no Sertão pernambucano - GUIMARÃES, Sara Alves de Carvalho Araújo (2020)
Preferential flow is an infiltration phenomenon that accelerates the water percolation of the soil. In natural soil, such as the caatinga, this flow occurs in macropore region formed by root canals, gallery networks made by macrofauna galleries, and continuous cracks in the soil profiles. The matrix part of the soil is responsible for storing and filtering water and dampening the preferential flow. The replacement of caatinga by pasture can considerably alter the structure of these soils and negatively interfere with their hydrological functions. This study's objective was to evaluate the parameters that control the generation of preferential and matrix flow of two land use, one caatinga dry forest and other pasture. For that, measurements of total saturated hydraulic conductivity (Ks,g), obtained using the Inverted Auger Hole method, and of the soil matrix (Ks,m), using the Beerkan and cylindrical monolith methods. The difference between Ks,g, and Ks,m allowed to obtain the preferential flow (Ks,f). The values of Ks, f in soils under caatinga exceeded those under pasture, showing that the change in land use significantly modifies this hydrodynamic property, favoring its degradation. The caatinga soils replaced by pasture lost the hydraulically active pore pathways induced by the activity of the roots, considerably decreasing the capacity of these soils to transmit water.